Habitat Use and Behavior of Multiple Species of Marine Turtles at a Foraging Area in the Northeastern Gulf of Mexico - Wildermann, Natalie E.; Sasso, Christopher R.; Stokes, Lesley W.; Snodgrass, Derke; Fuentes, Mariana M. P. B. (Frontiers in Marine Science, 2019)
Multi-species conservation strategies can be useful to maximize allocation of resources. To effectively plan for multi-species management practices, it is important to have a robust understanding of the variability in the spatial and behavioral ecology of sympatric species. To address this in the context of marine turtles, this study explored fine-scale habitat use by three sympatric species (juvenile green turtles (Chelonia mydas), Kemp’s ridley turtles (Lepidochelys kempii) and loggerhead turtles (Caretta caretta)) in a foraging area near Crystal River, Florida, USA. By combining sighting surveys and satellite tracking methods, we found that the distribution of the three species of marine turtles in this region overlapped both in space and time. We also observed differences in the fine-scale location of hotspots and in-water behavior among species, with some degree of apparent habitat partitioning. Habitat partitioning was particularly evident when assessing the diving and surfacing behavior of tracked turtles, with some degree of differentiation in diel diving patterns, particularly depths utilized during daytime/nighttime and the dive/surface duration. Our study provides ecological baseline data on the spatial overlap, habitat use and behavior of three sympatric marine turtle species, which can inform future management strategies at nearshore marine habitats in the Northeastern Gulf of Mexico.